The narrators whom Ibn Hibban trusted in his Sahih, and Al-Dhahabi agreed with him on his authentication - a critical study (Islamic Sciences Journal, 2025)
ABSTRACTThe science of criticism and authentication is one of the most important types of hadith sciences and it has a special interest and only the experts and experts in the hadith craft have delved into this science. Hence, the topic of my research was chosen, entitled (The narrators who were authenticated by Imam Ibn Hibban in his Sahih and Imam Al-Dhahabi agreed with his authentication - a critical study). I have inventoried the narrators and studied them and the statements of the scholars of criticism and authentication and scholars of hadith criticism. After that, I explained the most correct opinion in terms of the authentication of Imam Ibn Hibban and the agreement of Imam Al-Dhahabi.
Keywords: Narrators, trustworthy, Habban, Al-Dhahabi, wounded.